Imidazolium salt and dielectric barrier discharge plasma treatment to enhance the conductivity of fabrics impregnated with pedot:PSS - Magalhães, Cátia (2022)
Conductive textiles are a class of materials with a growing interest due to their potential applications in medical, healthcare, comfort, protective clothing, and sportswear sectors. They can be used for the development of smart textiles able to answer to different external stimuli such as thermal, mechanical, chemical, electrical, magnetic, and optical. The complex poly (3,4-ethylene dioxythiophene):polystyrene sulfonate (PEDOT:PSS) is the most explored polymer to prepare conductive textiles. Dopants can be introduced to add or remove electrons from the backbone of PEDOT:PSS, resulting in increased conductivity. Salts such as 1-butyl-3-methylimidazolium octyl sulphate (IZ) may promote ionic interactions with PEDOT:PSS, stimulating a microstructure reorganization. Moreover, the dielectric barrier discharge (DBD) plasma treatment has been shown to improve the adhesion of coatings by modifying the surface roughness, surface chemistry, and hydrophilicity of the fabrics. In this work, untreated and DBD plasma-treated polyester (PES) fabrics were impregnated with PEDOT:PSS with and without the addition of imidazolium salt (0.2M) as a dopant. Using the IZ, it was possible to adapt the textile materials into resistors, where the applied current converted electrical energy into heat. The developed textiles can be used to produce heating garments.